The Effect of Organisational Commitment in Mediating the Relationship between Transformational Leadership and Corporate Competitive Advantage (Study on State-Owned Companies in Indonesia) - Gatot Kustyadji (PT. Mawadaku Sukses Solusindo, 2023)
This study aims to test and analyze the relationship pattern of transformational leadership, organizational commitment, and corporate competitive advantage. The study was conducted in three Indonesian state-owned enterprises. Data will be collected by distributing a questionnaire to 156 managers. The number of questionnaires that can be used is 120. Data analysis is performed using a HE SEM equipped with AMOS as the data processing application. The results of this study show that: (1) Transformational leadership has a significant positive impact on organizational commitment. (2) Transformational leadership has a significant positive impact on a company's competitive advantage. (3) Organizational efforts have a significant positive impact on a company's competitiveness. (4) Organizational commitment mediates the impact of transformational leadership on a firm's competitive advantage.